All Days 2005
DOI: 10.2523/iptc-10987-ms
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Uncertainty in Production Forecast for Fields With Significant History: A West African Case Study

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractUnderstanding the impact of subsurface uncertainties on production responses is an integral part of the decision making process. A more accurate quantification of the uncertainty band around production forecasts contributes to better business decisions. Traditional experimental design workflows, where a limited set of models represent the key uncertainties in subsurface parameters, might be well suited for new field developments. However, when a field has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…76% of reserves. 'White' wells (1,2,4,8,10) show contributions of 23%, whilst 'grey' wells (3,7,9) will contribute only around 1%.…”
Section: Pressure History Matchmentioning
confidence: 99%
“…76% of reserves. 'White' wells (1,2,4,8,10) show contributions of 23%, whilst 'grey' wells (3,7,9) will contribute only around 1%.…”
Section: Pressure History Matchmentioning
confidence: 99%
“…In general, these algorithms can be categorized into two groups: (1) gradient-based methods such as the Gaussian-Newton method (Thomas et al 1972) and the Levenberg-Marquardt algorithm (Reynolds et al 2004); and (2) gradient-free methods including GAs (Castellini et al 2005) and simulated annealing (SA) algorithms (Sultan et al 1994). In order to obtain the gradient search direction, the gradient of the objective function is required, and it can be obtained by using an adjoint equation (Li et al 2001) or by computation of the sensitivity coefficient (Tan and Kalogerakis 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Gradients based methods showed less performance in history matching because of their tendency to get trapped in local minima. In stochastic methods, many authors have tried different algorithms like simulated annealing (SA) (Sultan et al, 1994), neighbourhood algorithm (NA) (Subbey et al, 2003), genetic algorithms (GA) (Castellini et al, 2005;Sangwai et al, 2007), scatter search (SS) (Sousa et al, 2006;Erbas and Christie, 2007), Markov chain Monte Carlo (McMC) (Maucec et al, 2007), particle swarm optimization (PSO) (Mohamed et al, 2009), ant colony optimization (Hajizadeh et al, 2011), differential evolution (DE) (Hajizadeh et al, 2010). It is observed that the differential evolution algorithm has shown good results for the history matching but the performance of the algorithm was very much sensitive to the value of control parameters such as crossover rate.…”
Section: Introductionmentioning
confidence: 99%